2009
DOI: 10.1088/1674-1137/33/7/018
|View full text |Cite
|
Sign up to set email alerts
|

X-ray beam hardening correction for measuring density in linear accelerator industrial computed tomography

Abstract: Due to X-ray attenuation being approximately proportional to material density, it is possible to measure the inner density through Industrial Computed Tomography (ICT) images accurately. In practice, however, a number of factors including the non-linear effects of beam hardening and diffuse scattered radiation complicate the quantitative measurement of density variations in materials. This paper is based on the linearization method of beam hardening correction, and uses polynomial fitting coefficient which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The diameter of the beads is 10 mm, which is based on the standard molar size. 31 The phantom was constructed by incorporating four metallic beads, which were alumina (Al 2 ) 34 and chromium (Cr, 7.9 g cm -3…”
Section: Orthopaedic Metal Artefact Reduction Phantommentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of the beads is 10 mm, which is based on the standard molar size. 31 The phantom was constructed by incorporating four metallic beads, which were alumina (Al 2 ) 34 and chromium (Cr, 7.9 g cm -3…”
Section: Orthopaedic Metal Artefact Reduction Phantommentioning
confidence: 99%
“…Owing to the high Z of these materials, metal streak artefacts in the CT image can be induced through the combination of beam hardening, scatter, photon starvation, partial volume effects and aliasing. [1][2][3][4][5] These artefacts cause systematic discrepancies between the true attenuation coefficients of the objects and the CT Hounsfield units (HUs) in the reconstructed image. 1 The discrepancies not only degrade diagnostic image quality but also compromise parts of the radiation treatment planning process such as structure delineation, treatment geometry definition and the extraction of the electron density distribution used for dose calculation.…”
mentioning
confidence: 99%
“…It was shown that additional filters increase image noise, which impaired the detectability of low-density materials. Zhou Ri-Feng et al [22] showed that in the energy range of 0.3-3 MeV, the value of μ e of a different substance is approximately the same, particularly for Fe and Cu, and the relative error is even less than 1%. Beam hardening correction using an X-ray pre-hardening filter of 2 mm iron and 1 mm copper was carried out using the CIVA simulation software.…”
Section: A Simulationmentioning
confidence: 99%
“…They described the process of estimating the equivalent monoenergetic data, m, from the total attenuation, p, representing the polyenergetic X-ray beam. Zhou Ri-Feng et al [22] compared the linearisation technique and hardware filtration for estimating material density, where a density measurement error of less than 2% is achieved by using pre-filters. Meganck et al [23] used beam filtration to minimise the BH artefact in micro-computed tomography for the estimation of bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation